2017
DOI: 10.1177/1687814017692290
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic characteristics of a novel catapult launched morphing tandem-wing unmanned aerial vehicle

Abstract: A novel morphing unmanned aerial vehicle with tandem-wing configuration could fold into a tubular catapult and deploy the four airfoils after launching. Because of the rapid deploying process, the aerodynamic characteristics will become largely different. Numerically investigating the aerodynamic characteristics at low Reynolds numbers (Re \ 10 6 ) is of great significance for control-stability analysis, control laws design, and overall design. By comparing the numerical simulation results of the different air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Most recently, CFD method has also been used by Gao and colleagues to investigate the unsteady aerodynamic characteristics of a catapult launched morphing tandem-wing UAV. 29 Results demonstrated that the deformation rate had significant influence on the aerodynamic coefficients and the hinge moments of both lifting surfaces; additionally, the rapider deformation rate caused higher variable quantity of the unsteady aerodynamic characteristics. Compared with CFD methods, theoretical calculations with higher efficiency can also be used to calculate the unsteady aerodynamics in the preliminary design of tandem-wing UAVs.…”
Section: Introductionmentioning
confidence: 93%
“…Most recently, CFD method has also been used by Gao and colleagues to investigate the unsteady aerodynamic characteristics of a catapult launched morphing tandem-wing UAV. 29 Results demonstrated that the deformation rate had significant influence on the aerodynamic coefficients and the hinge moments of both lifting surfaces; additionally, the rapider deformation rate caused higher variable quantity of the unsteady aerodynamic characteristics. Compared with CFD methods, theoretical calculations with higher efficiency can also be used to calculate the unsteady aerodynamics in the preliminary design of tandem-wing UAVs.…”
Section: Introductionmentioning
confidence: 93%
“…All chosen drones for comparison are roughly equal in Reynolds number. The first drone chosen is a catapult-launched tandem wing morphing unmanned aerial vehicle [32] (Team 1), the second is a fixed wing micro air vehicle (MAV) [17] (Team 2) and the last drone is a rotating wing micro air vehicle [16] (Team 3). The variation of the drag coefficient as a function of the angle of attack is presented in Figure 19, this figure represents a comparison of the results of the experimental measurements of the drag of the present heliplane and three other unmanned aerial vehicles.…”
Section: Comparisonmentioning
confidence: 99%
“…The equations can be linearised under the small disturbance theory and then aerodynamic forces and moments can be described by the Taylor series (Cook, 1997). In the case of unconventional configurations, the problem of estimation of aircraft flight dynamics by solving the eigenvalues problem was considered in Goetzendorf-Grabowski et al (2016), Goraj (2014) and Mieloszyk et al (2020).…”
Section: Introductionmentioning
confidence: 99%